PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA SD - Mundzir, Muhammad Fahri; Sujana, Atep; Julia, Julia (Jurnal Pena Ilmiah, 2017)
The research intend to know the sience literacy skill improvement of students with problem-based learning on high level, medium level, and low level. Methodology of research be used is pre-experiment with design (the one group pretestt-posttest design). The research is accomplishe at SDN Cimalaka, SDN Cibereum III and SDN Palasah. The instrument used in this research is by the science literation skill of science test with pretestt and posttest on each high, medium, and low levels, teacher’s achievement observation sheet, student activeness observation, and science attitude scale questionnaire. The research show that the problem-based learning could improve the science literacy skill of students in all levels, and it is proved by the result of mean difference test on high level measured 0.000, on medium level measured 0.000, and low level measured 0.001. It is mean that the learning method could improve the science literation skill of students in all levels